Effect of roasting on physicochemical and functional properties of flaxseed flour. Issue 1 (31st December 2016) - Khan, Azhar; Saini, C.S.
Abstract: An investigation was carried out on the physical, physicochemical, and functional properties of flaxseed. Physical properties viz. seed shape and size, geometric and arithmetic mean diameter, sphericity, aspect ratio, bulk and true density, porosity, angle of repose, and static friction coefficient were determined. Geometric and arithmetic mean diameter were 2.19 and 3.51 mm while average sphericity and aspect ratio were 40.34 and 62.58%. The average true density, bulk density, and porosity were 1.34 g/cm 3, .66 g/cm 3, and 51.56%. Angle of repose was 19.40° and coefficient of static friction obtained on glass, stainless steel, plywood perpendicular, and plywood parallel was .32, .36, .33, and .33, respectively. Flaxseeds were roasted and compositional and functional properties like water absorption capacity (WAC), oil absorption capacity (OAC), foaming capacity, foaming stability, sedimentation value, and least gelation concentration of roasted and unroasted flaxseed flour were performed. Foaming capacity (9.23%) and foaming stability (54.43%) were significantly higher for unroasted flaxseed than roasted flaxseed flour (7.82 and 48.60%). Roasted flour was observed to have highest values of WAC, bulk density, WSI, ash, fiber, carbohydrate, and lowest values of moisture, protein, fat, OAC, tap density, porosity, angle of repose, WAI, and sediment value as compared to unroasted flour.